A Study on the Love of William Wordsworth Towards Nature In His Poems: Exploring Wordsworth's Romantic Philosophy of Nature (Journal of Advances and Scholarly Researches in Allied Education, 2013)
As a poet of Nature,Wordsworth stands supreme. He is a worshipper of Nature, Nature’s devotee orhigh-priest. His love of Nature was probably truer and more tender, than thatof any other English poet, before or since. Nature comes to occupy in his poema separate or independent status and is not treated in a casual or passingmanner as by poets before him. Wordsworth had a full-fledged philosophy, a newand original view of Nature. Three points in his creed of Nature may be noted: